Simulasi Kemampuan Koneksi Kesalah Kode Kuasi Siklik Diperumum-LDPC Pada Channel Biner Simetris - Sukriadi, Muhammad (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2023)
Low Density Parity Check code or abbreviated as LDPC is a linear error correcting that is used to maintain the integrity of the data. This code is known to have error-correcting capabilities that are close to the maximum theoretical error-correction limit. LDPC code can be made efficient by hybridizing with generalized quasi-cyclic code. Quasi-cyclic codes are generalizations of cyclic codes. The error correction capability of this generalized quasi-cyclic code-LDPC is closely related to the decoding algorithm chosen for the LDPC code. The algorithm used in this research is the Log-Likelihood Ratio Sum-Product Algorithm or abbreviated as LLR-SPA. In this research, simulation of quasi-cyclic code error correction capability in general-LDPC is given on a symmetric binary channel. The main objective of this research is the maximum number of errors that can be corrected by a generalized quasi-cyclic code-LDPC on a symmetric binary channel. Based on the simulation, the main result is that the greater the number of errors added, the smaller the possibility of the message being received in its entirety.